Respuesta :
Answer:
Step-by-step explanation:
3x+4y=−23.........(1)
x=3y+1 .........(2)
Putting (2) in (1)
3(3y + 1) + 4y = -23
9y + 3 + 4y = -23
9y + 4y = -23 - 3
13y = -26
y = -26/13
y = -2
Putting y into (2)
x=3y+1
x = 3(-2) + 1
x = -6 + 1
x = -5
The solution to the equation is (-5, -2)
Given the system of equations
- 3x+4y=−23 ..... 1
- x=3y+1 ...... 2
Substitute eqn 2 into 1 to have:
3x+4y=−23
3(3y+1)+4y=−23
9y + 3 +4y = -23
13y = -26
y = -2
Since x = 3y + 1
x = 3(-2) + 1
x = -5
Hence the solution to the equation is (-5, -2)
Learn more on simultaneous equation: https://brainly.com/question/16863577